Development of biomass-derived cellulose for biodiesel production - Tok, Jia Kee (2022)
Biodiesel has emerged as a promising renewable substitute to conventional fossil fuel for diesel engines. In this regard, biomass-derived cellulose can be utilised as the raw material to fabricate an eco-friendly catalyst while reducing the overall production cost for biodiesel production. Therefore, the main focus of this study is to determine the potential applicability of biomass-derived cellulose catalysts in biodiesel production. From the study, it shows that the cellulose exhibits a porous structure with high surface area which can increase the reaction rate. The cellulose also has good mechanical properties as the XRD results indicate that the peaks at around 22 ° to 23 ° are attributed to the crystalline structure of cellulose with high crystallinity. Moreover, biomassderived cellulose catalyst is thermally stable up to 380 ℃. FTIR analysis has also confirmed the purity of the cellulose and the discruption of the cellulose linkages is found which can increase the porosity. On the other hand, biomassderived cellulose catalyst is able to produce biodiesel yield above 85 % under optimum conditions. Investigation on the kinetic characteristics reveals that the reaction obeys pseudo first-order law and the reaction rate constants increase with the temperature. It is discovered that the activation energy of the reaction catalysed by biomass-derived cellulose is lower than that of other non-cellulose catalysts, thus improving the catalysis in biodiesel production. In addition, the thermodynamic parameters are determined where the values of enthalpy change and Gibbs free energy change are positive, indicating the reaction is endothermic and endergonic. The negative values of entropy change shows that the disorder and randomness decreases during the reaction. Overall, the results conclude that biomass-derived cellulose catalyst exhibits excellent catalytic activity which is a potential sustainable catalyst to produce biodiesel.